Myoid gonadal stromal tumours are characterised by recurrent chromosome‐level copy number gains: molecular assessment of a multi‐institutional series. Issue 3 (27th October 2022) - Collins, Katrina; Sholl, Lynette M.; Siegmund, Stephanie; Dickson, Brendan C.; Colecchia, Maurizio; Michalová, Květoslava; Hwang, Michael; Ulbright, Thomas M.; Kao, Chia‐Sui; van Leenders, Geert J.L.H.; Mehta, Vikas; Trpkov, Kiril; et al.
Abstract : Myoid gonadal stromal tumours (MGST) represent a rare type of testicular sex cord‐stromal tumour that has recently been recognised as a distinct entity by the World Health Organization (WHO) classification of genitourinary tumours. MGSTs affect adult men and have been reported to behave in an indolent fashion. Histologically, MGSTs are pure spindle cell neoplasms that coexpress SMA and S100 protein. Given that the molecular features of these neoplasms remain largely undescribed, we evaluated a multi‐institutional series of MGSTs using DNA and RNA sequencing. This study included 12 tumours from 12 patients aged 28 to 57 years. Tumour sizes ranged from 0.6 to 4.3 cm. Aggressive histologic features, such as vascular invasion, necrosis, invasive growth, and atypical mitoses were invariably absent. Mitotic activity was low, with a median of less than 1 mitosis per 10 high power fields (HPF; maximum: 3 mitoses per 10 HPF). Molecular analyses did not identify recurrent mutations or gene fusions. All cases with interpretable copy number variant data (9/10 cases sequenced successfully) demonstrated a consistent pattern of chromosome arm‐level and whole‐chromosome‐level copy number gains indicative of ploidy shifts, with recurrent gains involving chromosomes 3, 6, 7, 8, 9, 11, 12, 14q, 15q, 17, 18q, 20, and 21q. Similar findings have also been recognised in pure spindle cell and spindle‐cell predominant sex cord‐stromal tumours without S100 protein expression. MGSTs are characterised by ploidy shifts and may be part of a larger spectrum of spindle cell‐predominant sex cord‐stromal tumours, including cases without S100 protein expression. Abstract : Myoid gonadal stromal tumor represents a recently recognized entity that comprises testicular sex cord stromal tumors with pure spindle cell morphology and co‐expression of SMA and S100 protein. Molecular analyses of a multi‐institutional series assessed in this study reveals that myoid gonadal stromal tumors are characterized by absence of recurrent somatic mutations and a recurrent pattern of chromosome‐level and chromosome arm‐level copy number gains.